Co-Integration and Contagion Effect in Republic of Tiongkok and Asean Stock Market during The Economic Slowdown in Republic of Tiongkok - Chalimah, Nur; Witiastuti, Rini Setyo (Universitas Negeri Semarang, 2020)
This study aims to find empirical evidence of the relationship of co-integration and contagion effect on the stock market in the People's Republic of Tiongkok and ASEAN during economic slowdown in the People's Republic of Tiongkok in 2015-2017. The samples in this study were the stock market of the People's Republic of Tiongkok, Indonesia, Laos, Malaysia, the Philippines, Singapore, Thailand and Vietnam. The data used in the study are secondary data from the Composite Stock Price Index obtained from www.bloomberg.com. The research method used in this study is Vector Autoregression (VAR). The test results show that economic slowdown in the People's Republic of Tiongkok has no effect on the average JCI of the People's Republic of Tiongkok and ASEAN. There is co-integration in the average JCI of the People's Republic of Tiongkok and ASEAN. The average Indonesian JCI is not affected by the JCI average of the People's Republic of Tiongkok and ASEAN. There is contagion effect on the average JCI of the People's Republic of Tiongkok and ASEAN. Based on the results of the study it were concluded that co-integration and contagion effects occurs on the average JCI in the People's Republic of Tiongkok and ASEAN when economic slowdown occurs.